Who's afraid of contemporary art an A to Z guide to the art world - An, Kyung; Cerasi, Jessica (New York, NY Thames & Hudson, 2017)
What is contemporary art? What makes it contemporary?" What is it for? And why is it so expensive? From museums and the art market to biennales and the next big thing, Who's Afraid of Contemporary Art? offers concise and pointed insights into today s art scene, decoding Artspeak," explaining what curators do, demystifying conceptual art, exploring emerging art markets, and more. The authors playful explanations draw on key artworks, artists, and events from around the globe, including extreme Chinese performances, the artist Damien Hirst, and the expanding art markets in Brazil, Russia, India, China, and South Africa. An A Z arrangement of themes take the reader through every aspect of contemporary art, from Art, what is it?" to Money, money, money!!," and art outside the art market with Zoning out." Who s Afraid of Contemporary Art? is filled with behind-the-scenes information on the contemporary art world, and is the perfect gallery companion and go-to guide on the next big thing.
Includes index.
Keywords: Art, Modern -- 21st century